Perancangan Indikator Sustainable MICE Sebagai Bentuk Kolaborasi Perguruan Tinggi dan Dunia Industri - Eko Susanto; Any Ariani Noor; Santosa Sanjaya; Tamara Herlinda Erwin; Sri Hastuti; Ratna Padmi Trihartanti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
This article was written based on the Bandung State Polytechnic Community Service (PKM) activity associated with the Association of Indonesian Exhibition Organizers (ASPERAPI) DPD West Java to provide solutions to problems implementing the sustainable principle of MICE in Indonesia. Considering the condition of Indonesia's MICE industry which is currently in a state of slowdown due to COVID -19, ASPERAPI DPD West Java has a need for guidelines for the sustainable implementation of MICE from the results of university academic studies. Following up on this, has carried out Community Service activities by the Bandung State Polytechnic with a Continuous Assessment Guide and provided training on the use of these instruments to administrators and members of the West Java Regional Management ASPERAPI as partners. This activity has resulted in partners' understanding of the application of the sustainable principle of MICE and the adoption of the Electronic Book for Sustainable Assessment Guidelines which will be used as a sustainable measure in organizing future exhibition activities.